The Relationship Between the Economic Development Levels of the Countries and Their Sporting Achievements in the 2020 Tokyo Olympics - Emre Belli; Yusuf Yağız Saraçoğlu (Journal of Educational Issues, 2024)
The purpose of this study is to investigate the relationship between the economic development and order of success of the countries ranked in the top 20 at the 2020 Tokyo Olympics. In this context, the total number of medals of the countries in the top 20 of the total number of medals in the Tokyo 2020 Olympics was selected as a sporting success, as an indicator of development, the countries’ Gross Domestic Product (GDP) levels were also considered. In order to investigate the relationship between sporting success and economic development; SPSS package program was used. The significance level was considered as p < 0.05. Correlation analysis was performed by selecting the total number of medals as a dependent variable, the gross domestic products as an independent variable, and the population as a control variable. Findings of this research, a relationship was found the Gross Domestic Product (GDP) of the countries and the number of medals obtained at the 2020 Tokyo Olympics. According to these findings, a relationship has been found between economic development of countries and the number of medals won at the 2020 Tokyo Olympics, which we can see as international sporting success.